Adapt: Telepresent Artistic Collaboratories. - Bromberg, Ellen; Birringer, Johannes (Interdisciplinary Humanities)
Explores collaborations between the disciplines of technology and dance in the U.S. Association for Dance & Performance Telematics' research and critical dialogue on performance and media in telematic space; Methods and processes for distance collaboration; Opportunities for creative production on the Internet.